Sintesis Zeolit-Karbon Aktif Berbasis Abu Boiler Pabrik Kelapa Sawit Sebagai Adsorben Asam Lemak Bebas dan Karoten pada Crude Palm Oil - Taranipa Marfitania; Yunianto; Hariyanto; Koko Pratama Saragih; Ria Januarti (Syntax Corporation Indonesia, 2024)
The application of palm shells and fibers as boiler fuel in palm oil mills is highly recommended to maintain a sustainable utilization cycle. The combustion of palm oil shells and fibers producing non-optimally utilized and managed ash generates a high potential for environmental pollution. This research aims to utilize palm oil mill boiler ash (ABKS) as raw material for zeolite/activated-carbon (ZKA) composite synthesis. ZKA composite uses as free fatty acids and carotenes adsorbent in the bleaching process of crude palm oil (CPO). Based on the results of characterization with EDX and XRD, ABKS contains Si; Al; C of 40.71%; 6.10%: 0.66% and indicates to contain quartz and cristobalite minerals. The calcination process with NaOH followed by a hydrothermal process at a temperature of 100 °C for 24 hours produces ZKA which is known from the results of characterization using XRD and EDX where the composite is indicated to contain analcime zeolite and carbon. Based on SEM characterization results, the morphology of the ZKA composite is porous and have good particle size distribution. Based on the results of analysis of free fatty acids and carotenes from CPO before and after bleaching, ZKA composite reduces 15.67% of free fatty acids and 16.34% of carotenes. The resulting composite has good adsorption capabilities for free fatty acids and carotenes and may be a solution for utilizing biomass waste as a circular economy application in the palm oil industry.